Bacterioplankton Diversity and Distribution in Relation to Phytoplankton Community Structure in the Ross Sea Surface Waters - Cordone, Angelina; D’Errico, Giuseppe; Magliulo, Maria; Bolinesi, Francesco; Selci, Matteo; Basili, Marco; de Marco, Rocco; Saggiomo, Maria; Rivaro, Paola; Giovannelli, Donato; Mangoni, Olga (Frontiers in Microbiology, 2022)
Primary productivity in the Ross Sea region is characterized by intense phytoplankton blooms whose temporal and spatial distribution are driven by changes in environmental conditions as well as interactions with the bacterioplankton community. However, the number of studies reporting the simultaneous diversity of the phytoplankton and bacterioplankton in Antarctic waters are limited. Here we report data on the bacterial diversity in relation to phytoplankton community structure in the surface waters of the Ross Sea during the Austral summer 2017. Our results show partially overlapping bacterioplankton communities between the stations located in the Terra Nova Bay coastal waters and the Ross Sea open waters, with a dominance of members belonging to the bacterial phyla Bacteroidetes and Proteobacteria. In the Terra Nova Bay coastal area microbial communities were characterized by a higher abundance of sequences related to heterotrophic bacterial genera such as Polaribacter spp., together with higher phytoplankton biomass and higher relative abundance of diatoms. On the contrary, the phytoplankton biomass in the Ross Sea open water were lower, with relatively higher contribution of haptophytes and a higher abundance of sequences related to oligotrophic and mixothrophic bacterial groups like the OMG group and SAR11. We show that the rate of diversity change between the two locations is influenced by both abiotic (salinity and the nitrogen to phosphorus ratio) and biotic (phytoplankton community structure) factors. Our data provides new insight into the coexistence of the bacterioplankton and phytoplankton in Antarctic waters, suggesting that specific rather than random interaction contribute to the organic matter cycling in the Southern Ocean.